Disruption of Paneth and goblet cell homeostasis and increased endoplasmic reticulum stress in Agr2−/− mice - Zhao, Fang (2009)
Anterior Gradient 2 (AGR2) is a protein disulfide isomerase that plays important roles in diverse processes in multiple cell lineages as a developmental regulator, survival factor and susceptibility gene for inflammatory bowel disease. Here, we show using germline and inducible Agr2−/− mice that Agr2 plays important roles in intestinal homeostasis. Agr2−/− intestine has decreased goblet cell Mucin 2, dramatic expansion of the Paneth cell compartment, abnormal Paneth cell localization, elevated endoplasmic reticulum (ER) stress, severe terminal ileitis and colitis. Cell culture experiments show that Agr2 expression is induced by ER stress, and that siRNA knockdown of Agr2 increases ER stress response. These studies implicate Agr2 in intestinal homeostasis and ER stress and suggest a role in the etiology of inflammatory bowel disease.